Non-vitamin K Antagonist Oral Anticoagulants vs. Warfarin at Risk of Fractures: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Gu, Zhi-Chun; Zhou, Ling-Yun; Shen, Long; Zhang, Chi; Pu, Jun; Lin, Hou-Wen; Liu, Xiao-Yan (Frontiers in Pharmacology, 2018)
Warfarin is a traditional oral anticoagulant for preventing thrombotic events in patients with atrial fibrillation (AF) and venous thromboembolism. Along with the widespread clinical use, the potential association between warfarin use and fracture risk have been addressed gradually. Non-vitamin K antagonist oral anticoagulants (NOACs), targeting thrombin or Xa factor, have been recommended as an optimal alternative due to their favorable property of thromboembolism prophylaxis and reduced bleeding risk. However, evidence of the fracture risk with NOACs use is limited. Therefore, the present study investigated this issue by a meta-analysis. Medline, Embase, Cochrane Library and the ClinicalTrials.gov Website were searched for randomized controlled trials (RCTs) that reported the fracture data of NOACs and warfarin. The primacy outcome was a composite of any fracture. Summary relative risks (RRs) and 95% confidence intervals (CIs) were calculated using random- or fixed-effects models according to between-study heterogeneity. Heterogeneity was assessed through I2 test and Q statistic, and the number of patients needed to treat (NNT) was calculated based on fracture incidence. Subgroup analyses were conducted according to individual NOACs, indications, and duration of follow up. Finally, 12 RCTs involving 89549 patients were included, among which 44816 (50%) receiving NOACs and 44733 (50%) receiving warfarin. Overall, 1139 (1.3%) patients including 515 NOACs users (1.1%) and 624 warfarin users (1.4%) developed fracture. Risk of fracture was significantly lower in NOACs compared to warfarin (RR: 0.82, 95%CI: 0.73-0.93, P=0.001), with a NNT of 333. No significantly decreased risk was detected according to fracture sites. Subgroup analysis confirmed that the estimate of decreased fracture risk was derived mainly from AF patients receiving long-term anticoagulation treatment. The meta-regression did not detect any potential confounding on fracture risk. No heterogeneity between the studies (I2=15.0%) and no publication bias was identified. In conclusion, the use of NOACs was associated with a lower risk of fracture compared to warfarin, but with a relatively low absolute risk reduction. Therefore, screening for the fracture risk should be considered before initiating anticoagulation treatment. For patients who are at high risk of fracture or expected long-term treatment of anticoagulation, NOACs may represent a preferable alternative to warfarin.